Extension of labor contracts and optimal backpay - Leif Danziger (Institute for the Study of Labor (IZA), 2006)
This paper explains why a union and a firm might settle on a contract duration that may later be extended and characterizes the optimal backpay for the holdout period. It is shown that the choice between concluding a shorter contract that may be extended and immediately concluding a longer contract depends on the prevalence of the different types of uncertainty in the economy. It is also shown that the optimal backpay reduces the negative impact of nominal uncertainty on a worker's real income, but increases the worker's exposure to idiosyncratic uncertainty
urn:nbn:de:101:1-20090406327
Keywords: 330; Tarifvertrag; Dauer; Lohnverhandlungstheorie; Theorie